2020
DOI: 10.1107/s2053230x20007232
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the SH3 domain of growth factor receptor-bound protein 2

Abstract: This study presents the crystal structure of the N-terminal SH3 (SH3N) domain of growth factor receptor-bound protein 2 (Grb2) at 2.5 Å resolution. Grb2 is a small (215-amino-acid) adaptor protein that is widely expressed and involved in signal transduction/cell communication. The crystal structure of full-length Grb2 has previously been reported (PDB entry 1gri). The structure of the isolated SH3N domain is consistent with the full-length structure. The structure of the isolated SH3N domain was solved at a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This stands in sharp contrast to the nSrc-loop structure of the Grb2-nSH3 domain. Whereas the nSrc-loop is well defined and interacts with Gab1 residues R 507 PV 509 in the Grb2-Gab1 497-528 complex, it is highly variable in NMR structures of the SOS1 1149-1158 Grb2-nSH3 complex, disordered in the Grb2 dimer structure and adopts differing crystal packing influenced conformations in structures of ligand-free Grb2-nSH3 (29,(46)(47)(48) , suggesting inherent flexibility of this loop. The nSrc-loop conformation observed in the present structure resembles that of a ligand-free Grb2-nSH3 structure in which the proline-rich C-terminus of a crystallographic neighbor interacts with the S3/nSrc-loop region, suggesting that this might be a preferred conformation for peptide bound Grb2 nSH3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stands in sharp contrast to the nSrc-loop structure of the Grb2-nSH3 domain. Whereas the nSrc-loop is well defined and interacts with Gab1 residues R 507 PV 509 in the Grb2-Gab1 497-528 complex, it is highly variable in NMR structures of the SOS1 1149-1158 Grb2-nSH3 complex, disordered in the Grb2 dimer structure and adopts differing crystal packing influenced conformations in structures of ligand-free Grb2-nSH3 (29,(46)(47)(48) , suggesting inherent flexibility of this loop. The nSrc-loop conformation observed in the present structure resembles that of a ligand-free Grb2-nSH3 structure in which the proline-rich C-terminus of a crystallographic neighbor interacts with the S3/nSrc-loop region, suggesting that this might be a preferred conformation for peptide bound Grb2 nSH3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Structural superposition of the C-traces of nSH3-Grb2 in complex with Gab 497-528 , the minimized average NMR structure of the nSH3-Grb2-SOS1 1149-1158 complex (yellow) and the crystal structures of the nSH3 domain of ligand-free Grb2 (blue) and of the two molecules in the asymmetric unit of ligandfree nSH3-Grb2 (red, chain A and violet, chain B) (29,46,47). In the ligand-free nSH3-Grb2 crystal structure, the proline-containing C-termini of two neighboring nSH3 domains interact with the binding site of chain B nSH3 by mimicking S1/S2-binding and S3/nSrc-loop-binding, respectively.…”
Section: (E)mentioning
confidence: 99%
“…Crystallographic studies of the GRB2 n-SH3 domain have revealed its dimeric structure, with chains A and B present in the asymmetric unit. The SOS1-binding site in chain A involves specific residues, including Tyr7, Phe8, Trp36, Pro49, and Tyr52 [ 103 ]. In contrast, the SOS1 pocket in chain B is observed in a complex with the KPHPG residues from the C-terminus of chain A.…”
Section: Overview the Proteins Interacting With The Grb2 Sh3 Domainmentioning
confidence: 99%
“…As an alternative, we employed a partially processed experimental SF file which has not been merged to high symmetry. This strategy was tested on the structure with PDB code 6sdf, for which we have the complete set of raw diffraction data (Bolgov et al, 2020).…”
Section: Using Unsymmetrized Datamentioning
confidence: 99%